Families with pediatric type 1 diabetes: A comparison with the general population on child well‐being, parental distress, and parenting behavior. Issue 2 (17th November 2019) - Van Gampelaere, Cynthia; Luyckx, Koen; van der Straaten, Saskia; Laridaen, Jolien; Goethals, Eveline R.; Casteels, Kristina; Vanbesien, Jesse; den Brinker, Marieke; Depoorter, Sylvia; Klink, Daniel; Cools, Martine; Goubert, Liesbet; et al.
Abstract: Aims: The aim of this study was to compare families with a child (2‐12 years) with type 1 diabetes (T1D) to families which are not confronted with chronic illness, with regard to children's well‐being, parental distress, and parenting behavior. In addition, differences were explored between families whose child has optimal vs suboptimal glycemic control. Methods: Mothers, fathers, and children of 105 families with pediatric T1D completed questionnaires assessing child well‐being, parental distress, and parenting. The control group consisted of 414 families without chronic illness. Results: With regard to child well‐being, children with T1D had more adjustment difficulties (as reported by mothers) and lower quality of life (QoL) (as reported by mothers and fathers), whereas children themselves (8‐12 years) reported higher QoL compared to controls. In terms of parental distress, mothers, but not fathers, of children with T1D reported more stress, anxiety symptoms, and depressive symptoms than controls. With regard to parenting behavior, parent reports revealed less protectiveness in fathers and less autonomy support and responsiveness in both parents as compared to controls. No differences were found in parent‐reported psychological control between parents of children with and without T1D, but children with T1D perceived lowered parental psychological control. Lastly, secondary analyses indicated that especially families with suboptimal child glycemic control showed more maternal distress and worse child well‐being (according to parents). Conclusions: Families confronted with pediatric T1D differ from families without chronic illness: childhood T1D impacts parental perceptions of child well‐being and differentially affects mothers' and fathers' distress levels and behaviors.